2015
DOI: 10.1371/journal.pone.0125677
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Vulnerable Atherosclerotic Plaque in Rabbits Using DMSA-USPIO Enhanced Magnetic Resonance Imaging to Investigate the Effect of Atorvastatin

Abstract: BackgroundRupture of an atherosclerotic plaque is the primary cause of acute cardiovascular and cerebrovascular syndromes. Early and non-invasive detection of vulnerable atherosclerotic plaques (VP) would be significant in preventing some aspects of these syndromes. As a new contrast agent, dimercaptosuccinic acid (DMSA) modified ultra-small super paramagnetic iron oxide (USPIO) was synthesized and used to identify VP and rupture plaque by magnetic resonance imaging (MRI).MethodsAtherosclerosis was induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…MPI, fluorescence imaging (FLI), and computed tomographic angiography (CTA) in an ApoE −/− mouse model confirmed high specificity and sensitivity of the particles and allowed quantitative assessment of the degree of inflammation. Finally, to identify vulnerable plaques and rupture plaques, dimercaptosuccinic acid (DMSA) was bound to ultra-small IONPs and showed high specificity and sensitivity for early detection of vulnerable plaques and ruptured plaques after injection into an atherosclerotic rabbit model [ 192 ].…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…MPI, fluorescence imaging (FLI), and computed tomographic angiography (CTA) in an ApoE −/− mouse model confirmed high specificity and sensitivity of the particles and allowed quantitative assessment of the degree of inflammation. Finally, to identify vulnerable plaques and rupture plaques, dimercaptosuccinic acid (DMSA) was bound to ultra-small IONPs and showed high specificity and sensitivity for early detection of vulnerable plaques and ruptured plaques after injection into an atherosclerotic rabbit model [ 192 ].…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…In addition to MRI contrast agents, IONs can also be used to assess the effects of drug interventions. Two research groups have reported the use of USPIONs to evaluate the effects of atorvastatin on plaque stability of vulnerable atherosclerotic rabbits. The results showed that atorvastatin could prevent plaque instability by suppressing the synthesis of total cholesterol (TC) in hepatocytes, upregulating the density and activity of LDL‐C receptors on the surface of hepatocytes, and downregulating VCAM‐1 expressions and MMP‐9 concentrations …”
Section: Applicationsmentioning
confidence: 99%
“…For example, Cormode et al [9c] developed a gold‐conjugated‐high‐density lipoprotein NP (Au‐HDL) contrast agent for characterizing macrophage burden, calcification, and stenosis of plaques in apolipoprotein E knockout (ApoE −/− ) mice by using a spectral CT system. In 2015, Qi et al evaluated the anti‐atherosclerosis efficacy of atorvastatin by injecting iron oxide NPs into atorvastastin‐treated New Zealand white rabbits and imaging the reduction in plaque size by MRI. Next, bio‐nanomaterials allow for packaging of elevated amounts of therapeutic agents in a compact nanostructure and facilitate their delivery to the plaques.…”
Section: Introductionmentioning
confidence: 99%